Asuhan Keperawatan pada Ny. S dengan Post Partum Spontan di Ruang Nusa Indah RSUD dr. Soeselo Kabupaten Tegal - Cut Ema Arnila; Tati Karyawati; Siti Fatimah (STIKES Columbia Asia Medan, 2024)
The post partum period is divided into three, namely early puerperium (immediate puerperium) or recovery period 0-24 hours after delivery, immediate puerperium (later puerperium) or recovery period 1-7 days after delivery and remote puerperium (later puerperium) or the period to recover and be completely healthy (Rohmah et al, 2022). The purpose of this paper is to find out and provide nursing care to Mrs. S with postpartum in the Nusa Indah ward, dr. Soeselo Hospital, Tegal Regency according to nursing standards. The method used is a descriptive method in the form of interviews, observations, documentation studies, library studies and literature. From the case review, it was found that the patient’s main complaint was pain in the stitches in the birth canal, P: pain when moving, Q: pain like being pressed, R: pain in the stitches in the birth canal, S: pain scale 5, T: intermittent. There were 2 diagnoses found, namely labor pain and knowledge deficit. Interventions are designed based on the theories in SDKI, SLKI and SIKI as well as on the client’s condition and can be implemented.